Appetite-associated responses to central neuropeptide Y injection in quail. (June 2018) - McConn, Betty R.; Gilbert, Elizabeth R.; Cline, Mark A.
Abstract: The appetite-associated effects of neuropeptide Y (NPY) have been extensively studied in mammalian models. Less knowledge exists for other vertebrate species including birds. The aim of this study was to determine the effects of central injection of NPY on feeding behavior and hypothalamic physiology in 7 day-old Japanese quail ( Coturnix japonica ). During the light cycle, intracerebroventricular injection of 1.9 pmol, 0.5, and 1.0 nmol doses of NPY did not affect food intake, 0.031 to 0.13 nmol increased food intake, and 2.0 nmol NPY decreased food intake, in comparison to vehicle injection. Multiple doses of NPY stimulated water intake, but when food was not available, water intake was not affected. When injected during the dark cycle, NPY did not influence food intake. NPY-injected chicks had more c-Fos immunoreactive cells in the arcuate nucleus of the hypothalamus (ARC) and greater hypothalamic agouti-related peptide and neuropeptide Y receptors 1 and 2 (NPYR1 and NPYR2, respectively) mRNA than vehicle-injected chicks. Within the ventromedial hypothalamus, NPY-treated chicks expressed less NPYR1 mRNA, within the dorsomedial hypothalamus less NPY mRNA, and in the ARC greater NPYR2 mRNA than vehicle-injected chicks. Lastly, quail injected with NPY increased feeding pecks, escape attempts, and time spent preening, while locomotion, the number of steps, and time spent perching decreased compared to chicks injected with the vehicle. Results demonstrate that NPY stimulates food intake in quail, consistent with mammals and other avian species, but with some unique responses at the molecular level that are not documented in other species. Highlights: Quail desensitize to central neuropeptide Y injection at a considerably lower threshold than other species. Increased food intake after neuropeptide Y was coupled to an increase in c-Fos immunoreactivity and NPYR2 mRNA abundance in the arcuate nucleus. Behavioral changes after central neuropeptide Y injection are indicative of a shift towards feeding behavior.